Editorial page and table of contents - Editorial Team (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
ORDINES MILITARES COLLOQUIA TORUNENSIA HISTORICA Yearbook for the Study of the Military Orders vol. XXX (2025) EDITORIAL TEAM Jochen Burgtorf, Editor in Chief, California State University Krzysztof Kwiatkowski, Editor in Chief, Uniwersytet Mikołaja Kopernika w Toruniu Grischa Vercamer, Editor in Chief, Universität Passau Anna Maleszka, Associate Editor, Uniwersytet Mikołaja Kopernika w Toruniu Gregory J. Leighton, Assistant Editor, Muzeum Zamkowe w Malborku EDITORIAL BOARD Anna K. Dulska, Universidad de Navarra Sylvain Gouguenheim, École normale supérieure de Lyon Hubert Houben, Università del Salento Alan V. Murray, University of Leeds SCIENTIFIC COUNCIL Udo Arnold, Rheinische Friedrich-Wilhelm-Universität Bonn Karl Borchardt, Monumenta Germaniae Historica, München Roman Czaja, Uniwersytet Mikołaja Kopernika w Toruniu Helen Nicholson, Cardiff University Jürgen Sarnowsky, Universität Hamburg Maria Starnawska, Uniwersytet Przyrodniczo-Humanistyczny w Siedlcach Kristjan Toomaspoeg, Università del Salento Technical Editing and Proofreading: Krzysztof Kwiatkowski, Anna Maleszka, Gregory Leighton, Anna Dulska, Jochen Burgtorf, Marta Palczewska CONTENTS STUDIES AND ARTICLES FROM THE 22ND ORDINES MILITARES CONFERENCE Helen J. Nicholson (Cardiff) The Inventories, Accounts, and Records of Debts for the Templars’ Estates in England and Wales, 1308‒1313, as a Source for the Everyday Lives of the Templars OTHER STUDIES Sara Lantos (Haifa), Gil Gambash (Haifa), Assaf Yasur-Landau (Haifa), and Rabei G. Khamisy (Haifa) Crusader Military Order Fortifications along the Carmel Coast Nicholas Coureas (Nicosia) Food and Drink among the Templars and Hospitallers of Lusignan Cyprus Anthony Luttrell (Bath) Hospital and Temple: 1291‒1314 Gion Wallmeyer (Bielefeld) A Sudden Change of Plans? Reassessing the Hospitallers’ Crusading Strategy in the Early Fourteenth Century Alan V. Murray (Leeds) Celibacy versus Love: A Contrastive Approach to the Absence of Women among Crusaders in Prussia (Thirteenth and Fourteenth Centuries) Gregory Leighton (Malbork) Between History and Memory: A Source Contribution to the Historiographical Tradition of the Teutonic Knights c. 1500, Part I BOOK REVIEWS AND BOOK NOTICES Regesten zu den Briefregistern des Deutschen Ordens IV: der Ordensfoliant 13. Herausgegeben und bearbeitet von Jürgen Sarnowsky. Beihefte zum Preußischen Urkundenbuch 6. Göttingen: V & R unipress, 2024 (by Satoshi Kozu) Karin Jedner. Die Deutschordens-Kommende St. Katharina in Köln im 13. Jahrhundert. Quellen und Studien zur Geschichte des Deutschen Ordens 91. Ilmtal-Weinstraße: VDG-Verlag, 2023 (by Thomas Krämer) Katalog pieczęci Archiwum Państwowego w Toruniu. H. III. Bearbeitet von Janusz Bonczkowski, Marcin Hlebionek, Mateusz Superczyński und Anna Wieczorkowska, herausgegeben von Marcin Hlebionek. Toruń: Towarzystwo Naukowe w Toruniu, 2023 (by Benedikt Weigand) The 1522 Siege of Rhodes. Causes, Course and Consequences. Herausgegeben von Simon David Phillips. The Military Religious Orders: History, Sources and Memory. Abingdon‒New York: Routledge, 2022 (by Jürgen Sarnowsky) Aleksander Pluskowski. The Teutonic Knights. Rise and Fall of a Religious Corporation. London: Reaktion Books, 2024 (by Kacper Panek) Marian Dygo. Mulier fortis. Studia nad Prologiem w „Vita Dorotheae Montoviensis” Jana z Kwidzyna. Warszawa: Wydawnictwo DiG, 2023 (by Radosław Biskup) Hospitallers and Others. Military and Social Encounters. Edited by Christie Majoros, Maria Bonet Donato, and Julia Pavón Benito. Crusades Subsidia. Abingdon‒New York: Routledge, 2025 (by Karl Borchardt) Udo Arnold. Zakon Niemiecki. Podstawy, regiony, osoby. Toruń: Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika w Toruniu, 2023 (by Michał Rejner) Maciej Dorna. Knights of Christ of Prussia, a forgotten 13th century military order. Tallinn: Eostre, 2024 (by Igor Waraksa) Anna K. Dulska. Malitia temporis? Personas, gobierno y entorno de la Orden de San Juan de Jerusalén en Navarra medieval. New York: Peter Lang, 2021 (by Nikolas Jaspert) Piotr Lasek and Wojciech Wółkowski. Conrada Steinbrechta pruskie zamki biskupie i kapitulne. Warszawa: Instytut Sztuki Polskiej Akademii Nauk, 2025 (by Krzysztof Kwiatkowski)